Bioaugmentation effects of endophytic bacteria on growth and nitrogen and phosphorus accumulation of willow - LIU Guiqing; YANG Dong; NI Qijun; LI Tingqiang; HAO Hulin; CHEN Bao; YANG Weidong; YANG Xiao’e (浙江大学学报. 农业与生命科学版, 2016)
Due to large biomass, submergence tolerance, rapid growth, well-developed root system and strong adaptability, willow (Salix matsudana) trees were not only widely used in ecological restoration of the heavy metal pollution, organic pollution and eutrophication, but also used as source of biomass energy. To expand the range of application and improve the economic value, it is necessary to enhance the biomass and nutrient accumulation of willow. Phyto-microbial remediation technology was widely used in recent years for it was environmentally friendly, low cost and high efficiency in restoration. With assistance of microbe, the efficiency of phytoremediation was significantly enhanced. Endophytic bacterium, a kind of microbe colonized in plant tissue without causing pathogenicity, could produce plant hormones like gibberellin and indole acetic acid (IAA) to promote plant growth.In this study, willow trees were inoculated by eight endophytic bacteria (SaMR12, SaZR4, SaMR10, SaNR1, SaCS20, SM03, SM05 and LM02) derived from hyperaccumulator Sedumalfredii, and the plant growth and accumulation of nitrogen and phosphorus were investigated. In hydroponics experiment, the willow cuttings were grown in 2.5 L Hoagland’s solution with physiology upward until root length was above 1 cm. And propagation of endophytic bacteria suspension was added to the vessel with final density of 1×108 CFU/mL. The bacterial solution was replaced after 3 days. The treatment without bacterial inoculation was used as a control. The willows were observed and determined after 2 months of culture.The chlorophyll contents, root morphology, shoot and root biomass, nitrogen and phosphorus accumulation showed significantly different among different endophytic bacteria treatments. Chlorophyll content was significantly increased by 15% and 14% with inoculation of SaMR12 and SaMR10 endophytic strains as compared with the control. After inoculation with LM02, SaNR1 and SaMR12, the root morphology was significantly improved. The total root length was increased by 163%, 136% and 66%, respectively. Root surface area was increased by 54%, 12% and 17%, and the number of root tips was increased by 54%, 44% and 48%, respectively. With the inoculation of LM02, SaMR12 and SaMR10, the total biomass of willow was increased by 234%, 43% and 54%, respectively. The accumulation of nitrogen and phosphorus nutrients was also significantly promoted. Shoot nitrogen accumulation was increased by 176%, 26% and 41%, and shoot phosphorus accumulation was increased by 109%, 12% and 30%, respectively, as compared with the control. The root nitrogen accumulation was increased by 8.3 times, 2.4 times and 3.4 times, and the root phosphorus accumulation was increased by 4.8 times, 2.1 times and 2.8 times, respectively, with the inoculation of LM02, SaMR12 and SaMR10. Meanwhile, the concentrations of nitrogen and phosphorus in eutrophic water were significantly decreased.It is concluded that LM02, SaMR10 and SaMR12 are more efficient in promotion of plant growth than other endophytic bacteria. These strains also show the enhancement of willow growth for bio-energy and improvement of phytoremediation efficiency, which have a broad application prospect.